Potensi Limbah Cair Organik Sebagai Bahan Baku Biogas Menggunakan Sistem Fermentasi Dua Tahap - Dewi, Mubarokah Nuriaini; Visca, Rinette (LPPM Akademi Minyak dan Gas Balongan Indramayu, 2020)
The high value of COD (Chemical Oxygen Demand) is one of the indicators of the burden of organic substance pollution in the wastewater food flavoring industry. COD values can be lowered by converting to biogas. In this study biogas was made through a two-stage fermentation system. At the first stage organic material is conditioned in an acidic state (pH = 4) with variable fermentation time: 2 days, 4 days, 6 days and 8 days. Then at each time fermented for 18 days at second stages. As a result, the amount of biogas volume produced is the same, namely: 7,5 L. However, the most amount of methane is produced at the time of fermentation phase one for 2 days, namely: 83%. While the lowest value is produced at the time of fermentation phase one for 8 days, namely: 70%. At the time of fermentation phase one for 8 days produced the highest hydrogen composition, namely: 9,023 %. The composition of methane at stage one for 4 days produces a higher value, namely: 81.431% compared to the single stage fermentation system, namely: 78.9 %.